A packet radio network design for field, mobile multimedia communications: Network configuration, radio channel access and network management. - Simard, François. (University of Ottawa (Canada), 1997)
Current trends in the field of communication systems engineering aim at integrating different communication media into a single, coherent system. In many cases, these communication systems can be implemented because of the availability of a fixed infrastructure capable of supporting the stringent demands of multimedia communications. In some applications, however, a requirement for multimedia communications exists but access to fixed infrastructure is either impractical or unavailable. For these applications, the packet radio network represents an excellent framework for the communication system design. We are interested in designing a packet radio network which can satisfy the requirements of such ad-hoc, mobile multimedia applications. Specifically, the following broad design issues are addressed in this thesis: determining the network connectivity map and maintaining it as it changes over time; efficiently sharing the common radio channel amongst all users; and managing the overall network such that traffic is reliably routed from source to destination. (Abstract shortened by UMI.)
Keywords: Engineering, Electronics and Electrical.